Mighty Baal: essays in honor of Mark S. Smith - Russell, Stephen C.; Hamori, Esther J.; Smith, Mark S. (Harvard semitic studies, 2020)
"Mighty Baal: Essays in Honor of Mark S. Smith is the first edited collection devoted to the study of the ancient Near Eastern god Baal. Although the Bible depicts Baal as powerless, the combined archaeological, iconographic, and literary evidence makes it clear that Baal was worshipped throughout the Levant as a god whose powers rivalled any deity. Mighty Baal brings together eleven essays written by scholars working in North America, Europe, and Israel. Essays in part one focus on the main collection of Ugaritic tablets describing Baal's exploits, the Baal Cycle. Essays in part two treat Baal's relationships to other deities. Together, the essays offer a rich portrait of Baal and his cult from a variety of methodological perspectives"--